De novo design of an intercellular signaling toolbox for multi-channel cell–cell communication and biological computation - Pei Du (Nature Portfolio, 2020)
Intercellular signalling is fundamental for the formation of complex structures from single cells. Here the authors design six orthogonal cell–cell signalling channels for cell consortia communication and bio-computation.